Relationship between Medical Examination Service Quality and Patient Satisfaction in Significant Hospital in Developing Country - Chu, Si Dung; Nguyen, Thuy Tran; Khong, Tan Sin (International Journal of Innovative Research in Medical Science, 2018)
Objective - The aim of this study to demonstrate that have relationship between healthcare service quality (SQ) and patient satisfaction (PS) in the new model of research, ensure method of mesuring quality by new tool’s base on customer expectation. Subject and method: The study obtained feedback from patients, measure consumers’ perceptions of healthcare quality in both functional and technical quality including, using the SERVQUAL instrument with five generic dimensions (the original 22 scores instruments) for functional quality to combinate with the 8 dimensions for technical quality; Beside, measure PS by Tool of Victorian Patient Satisfaction Monitor (VPSM) with 6 origin dimensions (25 scores instruments). Survey on General clinic department at the private general hospital in Vietnam country’s one developing country. The study refers to the period from December 2013 to Jan 2014. Result - Altogether 420 persons were interviewed and 396 patients were identified by stratified random sampling. Most outpatients whose length of stay in general clinic department in the Bachmai hospital. The firth method’s Measuring healthcare quality by functional and technical quality; The functional quality by SERQUAL intrument with 5 items (22 score) and Technical quality item (8 score). Servqual instrument had 5 items are the“Tangible”, “Reliability”, “Responsiveness”, “Assurance”, “Empathy” including and Technical quality item’s Technical Quality; After performing factor analysis, we have four elements are drawn: Reliability (FQA1) with 11 variables, Empathy (FQA2) with 4 variables, Tangible (FQA3) with 3 variables, and Technical quality(TQA) had 8 variables with highly Corrected Item-Total Correlation of PS and reliability coefficient. The second method’s measuring healthcare through Tool of VPSM with 6 origin dimensions. After performing factor analysis, we have six elements are drawn: Access and Admission Index (DVa), General Patient Information Index (DVb), Treatment and Related Information Index (DVc), Complaints Management Index (DVd), Physical Environment Index (DVe), Discharge and Follow-up Index (DVf).The relationship between patient satisfaction (PS) and service quality (SQ) with R = 0.811 (sig = 0.0001). Conclusion - The firth, Adjusted research model for the public hospital have four contruct from levels of customer satisfaction about service quality is influenced by the SERVQUAL (3 items are reliability, empathy, and tangibles with 18 scores) and Technical Quality intrument (8 scores) with total of 26 scores. The second, Adjusted research model for the public hospital by Tool of VPSM have sixcontruct from levels of patient satisfaction about service quality (6 itemswith origine 25 scores). There is a strongly positive relationship between patient satisfaction (PS) and service quality (SQ) with high significant, ensure method of mesuring healthcare service quality by new tool’s base on customer expectation.